Insights from a general practice service evaluation supporting a lower carbohydrate diet in patients with type 2 diabetes mellitus and prediabetes: a secondary analysis of routine clinic data including HbA1c, weight and prescribing over 6 years. Issue 2 (2nd November 2020) - Unwin, David; Khalid, Ali Ahsan; Unwin, Jen; Crocombe, Dominic; Delon, Christine; Martyn, Kathy; Golubic, Rajna; Ray, Sumantra
Abstract : Background: In a single general practice (GP) surgery in England, there was an eightfold increase in the prevalence of type 2 diabetes (T2D) in three decades with 57 cases and 472 cases recorded in 1987 and 2018, respectively. This mirrors the growing burden of T2D on the health of populations round the world along with healthcare funding and provision more broadly. Emerging evidence suggests beneficial effects of carbohydrate-restricted diets on glycaemic control in T2D, but its impact in a 'real-world' primary care setting has not been fully evaluated. Methods: Advice on a lower carbohydrate diet was offered routinely to patients with newly diagnosed and pre-existing T2D or prediabetes between 2013 and 2019, in the Norwood GP practice with 9800 patients. Conventional 'one-to-one' GP consultations were used, supplemented by group consultations, to help patients better understand the glycaemic consequences of their dietary choices with a particular focus on sugar, carbohydrates and foods with a higher Glycaemic Index. Those interested were computer coded for ongoing audit to compare 'baseline' with 'latest follow-up' for relevant parameters. Results: By 2019, 128 (27%) of the practice population with T2D and 71 people with prediabetes had opted to follow a lower carbohydrate diet for a mean duration of 23 months. For patients with T2D, the median (IQR) weight dropped from of 99.7 (86.2, 109.3) kg to 91.4 (79, 101.1) kg, p<0.001, while the median (IQR) HbA1c dropped from 65.5 (55, 82) mmol/mol to 48 (43, 55) mmol/mol, p<0.001. For patients with prediabetes, the median (IQR) HbA1c dropped from 44 (43, 45) mmol/mol to 39 (38, 41) mmol/mol, p<0.001. Drug-free T2D remission occurred in 46% of participants. In patients with prediabetes, 93% attained a normal HbA1c. Since 2015, there has been a relative reduction in practice prescribing of drugs for diabetes leading to a T2D prescribing budget £50 885 per year less than average for the area. Conclusions: This approach to lower carbohydrate dietary advice for patients with T2D and prediabetes was incorporated successfully into routine primary care over 6 years. There were statistically significant improvements in both groups for weight, HbA1c, lipid profiles and blood pressure as well as significant drug budget savings. These results suggest a need for more empirical research on the effects of lower carbohydrate diet and long-term glycaemic control while recording collateral impacts to other metabolic health outcomes.